Asupan Energi dan Pola Makan dengan Status Gizi pada Pasien Turbeculosis - Nurhalisa Umar; Safruddin; Rahmat Hidayat; Al Ihksan Agus (Window of Nursing Journal, 2025)
Tuberculosis sufferers experience a decrease in appetite so that it has an impact on weight loss. This study aims to determine the relationship between energy intake and diet with nutritional status at banggai health center. The type of research used is analytic research with a cross sectional approach. Sampling used in this study is to use a total sampling in order to obtain 30 samples. The instruments used are 24-hour recall questionnaire and food frequency questionnaire (ffq). Data processing and data analysis in the form of percentages and correlation analysis using the chi square method. The results of the analysis with the chi square test between energy intake and nutritional status showed p value = 0.279 so that there was no significant relationship between the variables. And the chi square test between diet and nutritional status showed p value = 1.814 so that there was no significant relationship between the variables studied. The conclusion in this study was that there was no significant relationship between energy intake and diet with nutritional status in pulmonary tb patients at banggai health center. It is hoped that the puskesmas will motivate people with pulmonary tb more in health activities such as counseling, counseling about balanced nutrition for sufferers.